The Psychological Effects of Patriarchy System on Main Female Character in the Novel of the Tenant of Wildfell Hall - Fhadli Noer (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2018)
Patriarchy system occurs in the era of Victoria and many woman experience the effects of this system. The aims of the study is to find out the effect of patriarchy system endured by many woman character in the novel The Tenant of Wildfell Hall. This research was conducted by using descriptive qualitative method. The data used by the researcher in this research were taken from Anne Bronte’s novel entitled The Tenant of Wildfell Hall which was published by Anne Bronte in 1848. Data were collected by reading intensively the novel and conducting library research to find some useful resources which relate to analyzed topic namely relate to the patriarchy system. The result of study showed that the patriarchy system found in the novel The Tenant of Wildfell Hall (1848) touches some basic institution in the society namely economic institution, education, religion, family, state institution and cultural values. Helen Graham, main female character in the novel experienced psychological effect because she has a sorrowful life since her marriage with Arthur Huntingdon and also in the novel, the effect of patriarchy system is also experienced by Milicent Hargrave, Ralphs Hattersley’s wife. Moreover, the effect of patriarchy system makes Helen take some actions and struggle against it as the reaction of the effect of the system to end her sad life, by running away from his husband’s house which it is taboo to be done by a woman in Victorian era. On the contrary, Milicent Hargrave decides to be an obedient wife and endures all the sufferings but at the end of the novel, her husband, Ralph Hattersley changes his attitude and becomes a loving husband and father.